Regular Education Teachers' Attitudes towards Inclusion in Oman - Jalal H. Hussien; Ibrahim Al-Qaryouti (Sultan Qaboos University, 2014)
The objectives of the study were to investigate regular education teachers' attitudes towards inclusion and their educational setting preferences for teaching students with disabilities. In addition, the impact of teachers' gender and teaching experience on the attitudes towards inclusion were examined. Seven hundred three Omani regular education teachers participated in this study. The findings suggest that the Omani regular education teachers held neutral behavior, cognitive, and affective attitudes towards inclusion; and a small minority of teachers believed that full inclusion in regular education classrooms or resource rooms were the best educational settings for educating the students with disabilities in comparison with other educational settings. Finally, the results indicated that there were significant relationships between teachers' gender, teaching experience, and educational settings preference for educating students with disabilities and teachers' attitudes towards inclusion.